Total polyphenol content and free radical scavenging activity of cornsilk (Zea mays hairs) - Nurhanan .A.R,; Wan Rosli .W.I,; Mohsin .S.S.J, (Universiti Kebangsaan Malaysia, 2012)
Total polyphenol content and free radical scavenging activity of cornsilk (Zea mays hairs) extracts were determined. Our result showed the total polyphenol content of methanolic and water extracts were 272.81 mgGAE/100 g and 256.36 mgGAE/100 mg dry plant, respectively. The total flavanoid content of methanolic extract (38.01 mg catechin equivalent/100 g) was significantly higher (p<0.05) than the water extract (4.11 mg catechin equivalent/100 g). In radical scavenging activity, the activity of methanolic extract was significantly higher (p<0.05) than the water extract. The methanolic extract scavenged at 81.7% of free radicals at 1000 μg/mL while the water extract showed 63.5% of inhibition. In conclusion, cornsilk contained high polyphenol components with strong free radical scavenging activity thus could be considered as potential source of natural antioxidant.